A new paradigm for the diagnosis and management of unknown primary tumors of the head and neck: A role for transoral robotic surgery1. (14th November 2012) - Mehta, Vikas; Johnson, Paul; Tassler, Andrew; Kim, Seungwon; Ferris, Robert L.; Nance, Melonie; Johnson, Jonas T.; Duvvuri, Umamaheswar
Abstract Objectives/Hypothesis: In 2% to 3% of patients with cancer metastatic to cervical lymph nodes, a primary tumor will not be found despite exhaustive diagnostic efforts. The treatment for these patients includes cervical lymphadenectomy followed by radiation to areas with increased risk of harboring a mucosal primary. Wide‐field radiation therapy increases the incidence of xerostomia and dysphagia. Localizing a primary tumor has thus both therapeutic and quality‐of‐life implications, allowing possible complete surgical excision, concentrated radiation therapy, and potential deintensification of adjuvant therapy. With improved visualization and freedom of motion, transoral robotic surgery (TORS) is an innovative surgical modality that allows resection of oropharyngeal subsites with minimal morbidity. Study Design: Retrospective chart review. Methods: Ten patients with unknown primary tumors of the head and neck were identified. All patients underwent a cervical biopsy, positron‐emission tomography/computed tomography, formal endoscopy, and bilateral tonsillectomy. When the initial endoscopy and biopsies did not localize a primary tumor, all patients underwent transoral robotic base of tongue resection. Results: Evaluation of the patients' oropharyngeal mucosa using the robot did not reveal an obvious lesion and no palpable tumors were appreciated in the resected specimens. In 9/10 (90%) patients, pathologic examination revealed invasive squamous cell carcinoma (SCCA) with a mean diameter of 0.9 cm. Conclusions: Unknown primary SCCA presents a diagnostic challenge to the head and neck surgeon. We present a small series of tumors that would have been treated as unknown primaries under traditional diagnostic and therapeutic algorithms. TORS base of tongue resection identified primary tumors in 90% patients with minimal morbidity. Laryngoscope, 2013